Necrolytic migratory erythema following prolonged continuous subcutaneous dasiglucagon administration: a rare dermatologic adverse event - Lucas Weschle; Jenny Potratz; Frank Rutsch; Alexander Humberg; Sandra Oesingmann; Andreas Pascher; Alexander S Busch; Katja Masjosthusmann (Endocrinology, Diabetes & Metabolism Case Reports)
Clinical management of congenital hyperinsulinism (CHI) remains a significant challenge due to its complex pathophysiology and the limitations of available therapies. Dasiglucagon, a synthetic glucagon analog, represents a novel approach to managing CHI, particularly in patients where conventional therapies fail. This report discusses a rare case of prolonged continuous subcutaneous dasiglucagon use in a neonate with CHI. Despite initial stabilization of glycemic levels, the patient developed necrolytic migratory erythema (NME), a rare dermatological condition associated with hyperglucagonemia, during dasiglucagon therapy. The patient further experienced severe malnutrition, zinc and amino acid deficiencies, and sepsis. Following the discontinuation of dasiglucagon therapy due to these severe side effects, the patient’s skin and nutritional status improved markedly. However, glycemic control required subtotal pancreatectomy. This report underscores the potential of dasiglucagon in CHI management but highlights the importance of close monitoring during prolonged therapy. Learning points: NME, a rare but severe condition, appears to be associated with prolonged continuous subcutaneous dasiglucagon therapy, requiring early recognition and intervention. Close monitoring is essential during prolonged continuous subcutaneous dasiglucagon therapy to detect potential adverse effects, focusing on dermatological conditions, nutrient deficiencies or signs of infection. Multidisciplinary care is crucial to manage CHI with dasiglucagon, ensuring a comprehensive approach that addresses both glycemic control and potential side effects.